Waste Chute System - Abu Ghnaim, Ashar; Baker, Rana; Hmady, Huda (My University, 2018)
This project is discussing a system for waste disposal in multi-story buildings. It is defining the garbage chute system and it is showing the advantages for this system. Chute system is solving many environmental and social problems that Palestine faces. The project takes Nablus City as case study, it makes a questionnaire to know people’s opinion about this system, and so the results were positive and support this system. The system can only applies on new buildings; it can start applying chute system in commercial buildings until it makes the people familiar with this system. This project will be presented to Nablus Municipality to convert the idea to reality, and it is easy to apply this system because Nablus municipality increases the waste fees in percent of 100%, so there is a good budget.